Effects of changes in diagnosis and registration on time trends in recorded childhood cancer incidence in Great Britain. - Kroll, M; Carpenter, L; Murphy, M; Stiller, C (2012)
BACKGROUND: Increases in recorded childhood cancer incidence are widely reported, but do not necessarily represent real increases in risk. Time trends might conceal underlying steps caused by changes in diagnosis and registration procedures. METHODS: Using records from the National Registry of Childhood Tumours 1966-2005 (N=54650), the age-sex-standardised rate for residents of Great Britain aged under 15 years was calculated by individual year of diagnosis for each cancer subtype, and the average annual percentage change (trend) was assessed. The timing of assumed step changes in rate was estimated by iterative Poisson regression, and compared graphically with the approximate timing of innovations previously identified from published sources. RESULTS: Estimated timing of underlying steps approximately coincided with the following relevant innovations: biochemical assays, mid-1980s (hepatic and germ-cell cancer); diagnostic imaging, mid-1980s to early 1990s (intracranial/intraspinal tumours, neuroblastoma, soft-tissue sarcoma); revised cancer registration scheme, 1971 (leukaemia, bone and soft-tissue sarcoma); mandatory registration, 1993 (intracranial/intraspinal tumours, retinoblastoma, melanoma/carcinoma); cancer registration improvements, 2001 (leukaemia, renal and hepatic cancer). CONCLUSION: While the possibility of some real change in risk cannot be excluded, for many cancer subtypes the estimated timing of underlying step changes in rate appeared to correspond with changes in diagnosis or registration procedures. Childhood cancer may have been considerably under-recorded in the past.